2007
DOI: 10.1586/14737159.7.5.481
|View full text |Cite
|
Sign up to set email alerts
|

FibroMAX™: towards a new universal biomarker of liver disease?

Abstract: Among the noninvasive alternatives to liver biopsy, several studies have demonstrated the predictive value and a better benefit-to-risk ratio than biopsy of five combinations of simple serum biochemical markers (the super combination being FibroMAX (BioPredictive, Paris, France) in patients at risk of chronic liver diseases: FibroTest (BioPredictive) for the quantitative assessment of fibrosis; SteatoTest (BioPredictive) for the quantitative assessment of steatosis; ActiTest (BioPredictive) for the quantitativ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
47
0
1

Year Published

2012
2012
2023
2023

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 54 publications
(48 citation statements)
references
References 52 publications
0
47
0
1
Order By: Relevance
“…По данным Т. В. Анто-новой и соавт., у больных ХГС при нормальной актив-ности трансаминаз выявлены корреляционные взаимосвязи между индексом гистологической актив-ности и содержанием ФНО-α, тогда как в случаях с выраженным синдромом цитолиза эти связи отсут-ствуют [7]. Тем не менее трансаминазы остаются мар-керами воспаления и фиброза печени, входя в биохи-мические гепатопанели, в том числе в ФиброМакс [23]. Нами выявлены значимые прямые корреляции концентрации ФНО-α и ИЛ-6 с маркерами цитолиза, ВН, ГК и индексом эластичности печени.…”
Section: результаты и обсуждениеunclassified
“…По данным Т. В. Анто-новой и соавт., у больных ХГС при нормальной актив-ности трансаминаз выявлены корреляционные взаимосвязи между индексом гистологической актив-ности и содержанием ФНО-α, тогда как в случаях с выраженным синдромом цитолиза эти связи отсут-ствуют [7]. Тем не менее трансаминазы остаются мар-керами воспаления и фиброза печени, входя в биохи-мические гепатопанели, в том числе в ФиброМакс [23]. Нами выявлены значимые прямые корреляции концентрации ФНО-α и ИЛ-6 с маркерами цитолиза, ВН, ГК и индексом эластичности печени.…”
Section: результаты и обсуждениеunclassified
“…66 The individual values are then entered into BioPredictive's website (www.biopredictive.com) and an algorithm calculates the results, which are presented as numeric estimates on a continuous scale ranging from 0.00 to 1.00. Table 8 displays the correspondence proposed by Morra et al 67 between FibroTest scores and the fibrosis stages identified by the METAVIR, Knodell, and Ishak fibrosis staging systems. FibroMAX combines the components of FibroTest with alanine aminotransferase, aspartate aminotransferase, total cholesterol, triglycerides, fasting blood glucose, height and weight, and presents on one sheet the scores for FibroTest, SteatoTest (which measures hepatic steatosis) and AshTest (which measures the degree of necroinflammatory activity of alcoholic origin).…”
Section: Fibrotest and Fibromaxmentioning
confidence: 99%
“…67 stated that the cost of FibroTest ranged from €90 to €300 and that of FibroMAX from €150 to €500. However, it seems likely that FibroTest will in the future be priced more competitively in relation to the ELF test.…”
Section: Anticipated Costs Associated With Non-invasive Testingmentioning
confidence: 99%
See 2 more Smart Citations